Efisiensi Operasional sebagai Mediator antara Likuiditas, Leverage, dan Profitabilitas Perusahaan Properti - Febriyanti, Silfiana; Citradewi, Adelina (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Purpose: This study aims to analyze how the role of operational efficiency in mediating the effect of liquidity and leverage on the profitability of companies in the property sector. This was done because of the phenomenon of the value of the shares of companies in this sector decreasing consecutively over the past three years. Method: This research is exploratory research with a quantitative approach, which tests theory through measuring variables with numbers and statistical data analysis. Data analysis techniques include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, path analysis, and F and t hypothesis tests. The research population is property sector companies listed on the IDX in 2022, with a sample of 52 companies selected using the purposive sampling methodResults: The results of this research show that liquidity and leverage have an effect on operational efficiency, liquidity and leverage have no effect on profitability, operational efficiency has an effect on profitability, and operational efficiency can mediate the effect of liquidity on profitability, but cannot mediate the effect of leverage on profitability.Implications: This research can be a reference for the management of property sector companies to pay more attention to their liquidity management and leverage. Novelty: The research uses operational efficiency as a variable to mediate the relationship between liquidity and leverage and corporate profitability. Operational efficiency provides insight into the extent to which companies can optimize the use of their fixed assets to achieve maximum financial performance.